Integration between art and science (An Art Appreciation of Nyawa Light Exhibition) / May Tasneem Nor Adzaman … [et al.] - Nor Adzaman, May Tasneem; Mokhtar, Mumtaz; Shaharuddin, Adiba Amanina; Ramli, Nurul Adiba (Universiti Teknologi MARA, 2019)
This study aspires to inform that collaborative artwork between art and science plays a crucial role to bridge the gap between art and science field. This research is to meet the objective such as study the contextual analysis based on the selected artwork from Nyawa’s light exhibition at the same time analyze the formalistic artwork and also interpret the aesthetical content of the selected artwork from Nyawa’s light exhibition. In the present paper, the research method is described by qualitative study through two different methods which are through interviews with three different artists from three different categories and also through close observation. The findings were that collaborative artwork between art and science exposed the idea of understanding between both fields. Regarding the statement the research create a communication platform through artistic visualization on a scientific theory that leads to new media exploration based on new ideology and invention.